2011
DOI: 10.1186/1742-4690-8-17
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular masking of the HIV-1 Rev NLS by the cellular protein HIC: Novel insights into the regulation of Rev nuclear import

Abstract: BackgroundThe HIV-1 regulatory protein Rev, which is essential for viral replication, mediates the nuclear export of unspliced viral transcripts. Rev nuclear function requires active nucleocytoplasmic shuttling, and Rev nuclear import is mediated by the recognition of its Nuclear Localisation Signal (NLS) by multiple import factors, which include transportin and importin β. However, it remains unclear which nuclear import pathway(s) predominate in vivo, and the cellular environment that modulates Rev nucleocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 49 publications
3
27
0
1
Order By: Relevance
“…It is noteworthy that importin ␤ was the first described receptor for HIV-1 Rev nuclear import in vitro through its direct interaction with the atypical monopartite, arginine-rich NLS of Rev (58,68). Importin ␤ also has been shown to be an important Rev receptor in vivo (26). Therefore, we wished to determine whether importin ␤ alone could also mediate the nuclear import of BIV Rev.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that importin ␤ was the first described receptor for HIV-1 Rev nuclear import in vitro through its direct interaction with the atypical monopartite, arginine-rich NLS of Rev (58,68). Importin ␤ also has been shown to be an important Rev receptor in vivo (26). Therefore, we wished to determine whether importin ␤ alone could also mediate the nuclear import of BIV Rev.…”
Section: Discussionmentioning
confidence: 99%
“…The shuttling of HIV-1 Rev into the nucleus is mediated by the direct binding of the protein to the nuclear transport receptors, mainly importin ␤ but also transportin, importin 5, and importin 7 (3). Recent studies showed that importin ␤ and transportin import pathways are at play for the nuclear import of HIV-1 Rev in vivo (26,31). Moreover, the transportin pathway depends on the Nup358 nucleoporin that acts as a dock station (31).…”
mentioning
confidence: 99%
“…Gu et al (77) characterized the nuclear import characteristics of the HIV-1 derived Rev peptide across different cell lines, with results suggesting that HeLa, U937 and THP-1 cell lines employed transportin as the major transport receptor to rev, whereas in 293T, Jurkat or CEM cell lines, importin-β was the primary mediator of nuclear uptake. Intranuclear transport characteristics are also known to alter once cells become cancerous (78,79) .…”
Section: Cellular Characteristicsmentioning
confidence: 99%
“…Consistent with the concept of an additional class of karyopherin ␤1-and ␤2-dependent regulated NLSs, recently, the HIV-1 Rev protein was shown to import into the nucleus by both karyopherin ␤1-direct (24) and karyopherin ␤2 pathways, with a binding factor that regulates these NLS-transport factor interactions (25). Other proteins, such as the c-Jun oncoprotein, have been seen to interact with both karyopherin ␤1 and ␤2 as well as other import factors in vitro, via a basic stretch of amino acids, but without the PY epitope of a karyopherin ␤2-dependent NLS (26,27).…”
Section: Discussionmentioning
confidence: 66%